Changes in leg spring behaviour, plantar loading and foot mobility magnitude induced by an exhaustive treadmill run in adolescent middle-distance runners. Issue 2 (March 2015) - Fourchet, François; Girard, Olivier; Kelly, Luke; Horobeanu, Cosmin; Millet, Grégoire P.
Abstract: Objectives: This study aimed to determine adjustments in spring–mass model characteristics, plantar loading and foot mobility induced by an exhaustive run. Design: Within-participants repeated measures. Methods: Eleven highly-trained adolescent middle-distance runners ran to exhaustion on a treadmill at a constant velocity corresponding to 95% of velocity associated with VO2max (17.8 ± 1.4 km h −1, time to exhaustion = 8.8 ± 3.4 min). Contact time obtained from plantar pressure sensors was used to estimate spring–mass model characteristics, which were recorded (during 30 s) 1 min after the start and prior to exhaustion using pressure insoles. Foot mobility magnitude (a composite measure of vertical and medial–lateral mobility of the midfoot) was measured before and after the run. Results: Mean contact area (foot to ground), contact time, peak vertical ground reaction force, centre of mass vertical displacement and leg compression increased significantly with fatigue, while flight time, leg stiffness and mean pressure decreased. Leg stiffness decreased because leg compression increased to a larger extent than peak vertical ground reaction forces. Step length, step frequency and foot mobility magnitude did not change at exhaustion. Conclusions: The stride pattern of adolescents when running on a treadmill at high constant velocity deteriorates near exhaustion, as evidenced by impaired leg-spring behaviour (leg stiffness) and altered plantar loading.